The factors of influencing customer experience towards service quality of insurance agents - Lau, Hui Yi (2022)
As customers wish to receive a better customer experience nowadays especially in service quality of insurance agents. The purpose of conducting this research is to distinguish the factors that influence the customers experience towards service quality of insurance agents. Hence, Customer Experience Theory and Service Quality Concept were implemented to examine customer experience in receiving service from insurance agents. Using Customer Experience Theory and Service Quality Concept as a reference, Tangibility, Reliability, Responsiveness, Assurance, Empathy, Competence and Communication will be the manipulated variables and Customer Experience will be the responding variable. Seven hypotheses were formulated to distinguish the relationship between the variables. Questionnaires were ready using Google Form and dispersed to 300 respondents who have experience in receiving service quality from insurance agents. The data accumulated from respondents were analyzed and decoded using SPSS software. Besides, theoretical and managerial implications were projected with the trust that future investigators can treat it as source for observational way to advance discernment customer experience towards service quality of insurance agents.